Discourse - Howarth, David (New Delhi, 2002)
The concept of discourse provokes considerable debate and is understood in a variety of ways in the contemporary social sciences. This text presents a comprehensive overview of the different conceptions and methods of discourse analysis, while setting out the traditions of thinking in which these conceptions have emerged. It surveys structuralist, post-structuralist and post-Marxist theory, and the author sets out a fresh approach to discourse analysis, drawing principally on the writings of Saussure, Lévi-Strauss, Gramsci, Althusser, Foucault, Derrida, Laclau and Mouffe. He evaluates a number of pertinent criticisms of this approach, and explores ways in which discourse analysis can assist our understanding of identity formation, hegemony, and the relationship between structure and agency. This concise and engaging text provides a stimulating introduction to the concept of discourse for students and researchers across the social sciences.
Keywords: Structuralism